Technological Deployment and its Effect on Credibility of Elections in Nigeria under the Fourth Republic - Layiwola, Wahab Shehu (Kashere Journal of Politics and International Relations, 2023)
This paper investigates the role of technology in Nigeria’s electoral process during the Fourth Republic, employing a qualitative research design and drawing on the cybernetics model of communications theory as its theoretical framework. Through interviews with ten experts in technology deployment in the electoral process, the study reveals a consistent increase in technological integration since 2003, with various technologies addressing electoral challenges. The pivotal moment in 2015 marked the introduction of technology for Election Day activities, particularly voter accreditation, and the COVID-19 pandemic further accelerated its adoption. The paper found out that despite challenges like technological glitches and political interference, technology has positively impacted the electoral process by addressing issues such as multiple registrations and manipulation of results, leading to a reduction in electoral violence. The paper recommends the need for sustained commitment to technological enhancement, including investing in advanced equipment and updating software, to address challenges and ensure trustworthy election outcomes. Additionally, comprehensive training programs and legal reforms are recognized as crucial for adapting existing frameworks to the evolving technological landscape and creating a secure, free, fair and regulated credible election for an enhanced democracy.